Thyroid hormone alters the DNA binding properties of chicken thyroid hormone receptors alpha and beta. - Andersson, M L (1992)
The effects of thyroid hormone agonists on thyroid hormone receptor (TR)/DNA complex formation was investigated to elucidate the mechanism by which TRs transactivate genes in response to ligand. The data, obtained from gel shift experiments, indicate that thyroid hormones alter the conformation of TRs bound to DNA, irrespective of if the element is occupied by monomeric TR, homodimeric TR/TR, or heterodimeric complexes with the retinoid receptors RAR or RXR. Furthermore, triiodo-thyronine (T3) prevents 2 TR molecules from binding to oligonucleotides containing direct repeats or inverted palindromes of the consensus AGGTCA motif, an effect that was not detected with palindromic elements. Heterodimers bound to direct repeats were less affected: RXR/TR were fully and RAR/TR complexes partially resistant to thyroid hormone. The data suggest that a ligand-induced conformational change in TR prevents double TR occupancy of a response element containing 2 direct repeats of the consensus binding motif, possibly by steric hindrance, whereas such an event does not prevent TR/RXR heterodimers from binding to DNA. Finally, our data show that a monomeric, liganded TR bound preferentially to the second half site in a AGGTCActcaAGGTCA element, and therefore indicate that nucleotides adjacent to the consensus half site contribute to binding specificity.